Evidence of transactional capability in two different countries. Issue 4 (10th June 2019) - Hernani-Merino, Martin; Tello-Gamarra, Jorge
Abstract : Purpose: The aim of this study is to identify and analyze empirical evidence, which verifies the existence of the transactional capability construct in firms of financial systems in two different countries. Design/methodology/approach: This study investigates how the dimensions, and sub dimensions, of the transactional capability construct are reflected in the design of contracts. When analyzing the information from personal consumption loan contracts of nine Spanish firms and ten Peruvian firms in the financial system of each country, generalizable evidence of the transactional capability can be identified. Findings: The main result of this study is the identification of empirical evidence that proves the existence of transactional capability in financial markets with different characteristics. Research limitations/implications: This study was limited by a lack of similar research, which hampered the task of identifying and defining the dimensions that form the transactional capability construct. Originality/value: The identification of transactional capability was based on the analysis of contracts of personal credit consumption in the Peruvian and Spanish financial systems.